Navigating the boundaries of active global citizenship - Lough, Benjamin J; McBride, Amanda Moore (Transactions - Institute of British Geographers (1965), 2014)
This paper informs the active global citizenship debate by assessing whether returned international volunteers with a strong belief in the need for global governance also believe that participation in national political and civic spaces can drive global change. Regression models use survey responses from 245 returned international volunteers at three points in time. Findings indicate no significant difference in volunteers' conceptions of global citizenship before and after international service. However, volunteers who hold cosmopolitan views about the need for global governance have a higher sense of efficacy that participation in national spaces may affect global change. In addition, they are more likely to engage internationally but not locally. Findings suggest that global citizens may maintain an active civic identity rooted in overlapping locations. In addition, heightened notions of global citizenship appear to have a significant effect on returned volunteers' interest in international affairs and active engagement across national borders.